Von Heroen und Individuen: Sozialistische Mytho-Logiken in DDR-Prosa und DEFA-Film - Elit, Stefan (transcript, 2017)
The aporia of socialist individualism – In conjunction with Barthes, Blumenberg and Lévi-Strauss, Stefan Elit reads GDR novels and movies as paradoxical ways of dealing with mythological cultural politics.